Development of Science Teaching Materials on Inquiry-Based Biotechnology Materials Using the Addie Model for Class IX Students of SMP Negeri 3 Taman - Triana Nahrin Mahmudah; Iskandar Wiryokusumo; Ibut Priono Leksono (Buana Pendidikan, 2023)
There are still many educators who use teaching materials from publishers without planning, preparing, and compiling them themselves. So that learning science in the field for students is not used to using their reasoning power, but instead they are used to memorizing which is fixated on source books. The teaching material development model used is inquiry-based with the ADDIE model. The data instruments used were validation sheets/questionnaires and written tests. The results of the data were analyzed qualitatively and quantitatively. The data used in the form of scores on validation sheets and questionnaires were analyzed and processed with percentages and then converted into achievement scales. The teaching materials developed were then validated by a content expert with a result of 96% in the very good/very feasible category. The validation results from the design expert were 89.2% in the very good/very feasible category. Then the teaching materials developed were tested individually with a result of 98.3% in the very good/very feasible category. Small group trials 85.8% in the very good/very feasible category, field trials with 91.3% very good/very feasible results. class IX students